In Vitro Sporulation, Cultural Characterization, Identification And Phylogeny Of Gray Mold Fungus [Botryotinia Ricini (Godfrey) Whetzel.)] Of Castor (Ricinus Communis L.) (Applied Biological Research, 2018)
Control of Botryotinia ricini (Godfrey) Whetzel., gray mold pathogen of  castor, is a challenge due to the lack of known sources of complete resistance  and effective disease management practices. Isolation of pure culture of  causal pathogen and its profuse sporulation are imperative for any  pathological or molecular understanding of infection or resistance  mechanisms and host-pathogen interactions. Season-dependent disease  occurrence coupled with sparse conidial production in vitro has been a  serious constraint. A culture medium (BRS) based on V8 juice broth  supplemented with salts and minerals was developed and culture method and  conditions optimized for profuse in vitro sporulation of gray mold fungus.  ITS barcoding identified the isolate from Hyderabad as Amphobotyrs ricini  A. ricini isolate IRHT-S1) which was closely related to A. ricini strain Cop Ar5. Phylogenetic analysis of the isolate with 20 related fungal species  revealed that A. ricini forms a separate clade. Studies on growth response,  culture characteristics and sporulation of A. ricini in different media ingredients revealed that the culture morphology differed with medium composition, especially in medium with 60 g L-1 dextrose, while capsule/ epicarp extract was dispensable. The addition of salts such as MgSO4 (1.0 g  L1), KCl (1.0 g L-1) and FeSO4.7H2O (0.02 g L-1) favoured sporulation.
Keywords: Amphobotrys ricini; anamorph; culture medium; sporulation; ITS sequence